2016
DOI: 10.1002/adfm.201603197
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterials Act as Enhancers of Growth Factors in Bone Regeneration

Abstract: Inspired by the physiological events of the “wound healing cascade”, the integration of biomaterials and growth factors is generally accepted as an emerging and powerful strategy for bone regenerative therapy. As a type of biological mediator, growth factors play a key role in functional bone regeneration. In this review, recent progress in the enhancement of bone‐related growth factors via a biomaterial strategy will be discussed. Two main reinforcing mechanisms, temporal regulation and efficacy manipulation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
81
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 166 publications
(129 reference statements)
0
81
0
Order By: Relevance
“…The ideal bone substitute materials should possess biodegradability to create space for new bone tissue and eventually be replaced by mature bone tissue, preferably in a controlled manner . The degradation result showed that all the composite cements could degrade gradually in PBS and presented various degradability with different CS contents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ideal bone substitute materials should possess biodegradability to create space for new bone tissue and eventually be replaced by mature bone tissue, preferably in a controlled manner . The degradation result showed that all the composite cements could degrade gradually in PBS and presented various degradability with different CS contents.…”
Section: Discussionmentioning
confidence: 99%
“…The ideal bone substitute materials should possess biodegradability to create space for new bone tissue and eventually be replaced by mature bone tissue, preferably in a controlled manner. 31,32 The degradation result showed that all the composite cements could degrade gradually in PBS and presented various degradability with different CS contents. As the material degradability primarily depended upon the chemical composition and physical characteristic, the higher degradability of the C 3 S/SA/CS composite cements with higher CS content could be attributed to the rapid biodegradability of CS and the less compact microstructure.…”
Section: Discussionmentioning
confidence: 99%
“…Infection, trauma, and tumors can also lead to bone defects. limitations from traditional treatment of bone defects are considered as a significant clinical challenge to most of the orthopedic surgeons . Although autologous bone grafts are currently the most widely used bone defects treatment, they have limitations which may lead to complications such as donor site morbidity and graft failure.…”
Section: Introductionmentioning
confidence: 99%
“…Proper incorporation of these chemical cues within tissue scaffolds directly impacts new tissue formation, and it has been shown extensively that several different GFs often operate synergistically to facilitate or inhibit tissue growth. (1014) Additionally, correctly controlling the release and temporal presentation of growth factors is critical to ensure that functional tissues are developed with the desired phenotype. In order to progress from simple, thin tissues to highly heterogeneous tissues, interfacial regions, and whole organs, both spatial and temporal concentration profiles and gradients must be well understood.…”
Section: Introductionmentioning
confidence: 99%